Social Science Learning Management Based on InstillingHeroism Values at SDN Pendrikan Kidul 1 Semarang - Sugiyo, Sugiyo (2012)
There are three objectives of this research. The first is describing the characteristics of the lesson plan of Social learning based on heroism value establishment at SDN Pendrikan Kidul 1 Semarang. Secondly, it is describing the characteristics of Social learning based on heroism value establishment at SDN Pendrikan Kidul 1 Semarang. finally, the research aims at classifying the characteristics of Social learning impact based on heroism value establishment at SDN Pendrikan Kidul 1 Semarang. It is qualitative research using ethnography design. This research was conducted at SDN Pendrikan Kidul 1 Semarang. The informants are the principal and teachers of SDN Pendrikan Kidul 1 Semaranng. Techniques used in data collection are interview, observation, and documentation. Data analysis of this research includes data reduction, data display, and conclusion. Data validity uses credibility, transferability, confirmability and dependability. The research results show that (1) writing of Social lesson plan based instilling heroism value at SDN Pendrikan Kidul 1 Semarang is conducted based on the Education Unit Level Curriculum (KTSP). The lesson plan is elaborated from syllabus with emphasizing on attitude and heroism moral. Teachers prepare several components in writing the lesson plan that consists of Standard competence, Basic Competence, prop and source, and the assessment. In writing lesson plan, teachers consider the environment where teachers design learning with asking students to go to the heroic places such as palagan Ambarawa and Ronggowarsito. But teachers do not involve the computer-based media in Social lesson plan based instilling heroism value. (2) Social learning based heroism value establishment at SDN Pendrikan Kidul 1 Semarang run effectively. Teachers do several efforts to make the learning run effective such as discussing the important of instilling heroism value and the appropriate way in delivering material through Focus Group Discussion (FGD). The main materials delivered are focused on instilling the attitude and moral. Learning includes teaching and learning activities, habituation activities such as instilling discipline attitude and willing to sacrifice for students, and activities held by the school such as scout, and flag ceremony. Sources of material in the implementation of Social learning based instilling heroism value still use printed books not materials from internet. (3) Social learning based instilling heroism value has a positive impact for SDN Pendrikan Kidul 1 Semarang. With the heroism value establishment, students more understand on the values and spirit of heroism. Heroism spirit can be seen from the students' attitude such as being responsible, willing to sacrifice, and being a patriot.